EROSION’S NUMERICAL SIMULATION ON SOLID PARTICLES IN LIQUID-SOLID TWO-PHASE FLOW OF TEE PIPES - CHEN Yu; MA GuiYang (Jixie qiangdu, 2019)
Aiming at the problem of erosion in oil pipeline transportation system on solid particles in liquid-solid two-phase flow of tee pipes,the erosion area which is caused by solid particles what contain in oil can be simulated by using DPM erosion prediction model.Results show that the erosion location and the degree of solid particles are different from different types of tee pipe.The erosion of T pipe is mainly concentrated on the bottom of the horizontal pipe and the pipe wall near them.The erosion of tee pipe which has a sphere elbow is mainly concentrated on the horizontal pipe wall near the sphere,and the erosion degree is relatively small.